Linear acceleration in direct head contact across impact type, player position, and playing scenario in collegiate women's soccer players - Lamond, L. C.; Caccese, J. B.; Buckley, T. A.; Glutting, J.; Kaminski, T. W. (Journal of Athletic Training, 2018)
Context: Heading, an integral component of soccer, exposes athletes to a large number of head impacts over a career. The literature has begun to indicate that cumulative exposure may lead to long-term functional and psychological deficits. Quantifying an athlete's exposure over a season is a first step in understanding cumulative exposure.